Preparation and Characterization of Antimony-Doped Tin Oxide Nanocrystallite Coatings on 316L Stainless Steel - Nguyen Truong, Giang; Hoang Vinh, Long; Huynh Thu, Suong; Nguyen Thi Hong, Phuong; Nguyen Quang, Bac (Journal of Analytical Methods in Chemistry, 2021)
The study on the coatings containing antimony-dope tin oxide mostly has been done on titanium and its alloys for preparation of electrode materials. In this study, we try to prepare the similar coatings on 316L stainless steel, which is more common than titanium, and investigate some characteristics of the formed coatings. The preparation of the coating is by the impregnation of the substrate in solution containing SnCl4 and SbCl3 with the ratio of 93/7, and the concentration of SbCl3, 10 g/L in isopropanol, pH of 1–1.2, and the annealed temperature of 450°C give suitable coating for electrode materials. Some coating features, such as the crystal structure (XRD), morphology (SEM), hardness, electrical resistant, and electrochemical behaviors of the coating on the substrate have been also investigated. The results of the study show that the coatings can be used as electrode materials for the effective treatment of organic colorants in water such as methylene blue in water treatment.